ESTABLISHMENT OF DINUGUAN PUTOH KIOSK IN BATASAN HILLS QUEZON CITY - Dacut, Jennylyn G.; Jolina G. Sarcon; Reziel B. Padua; Maricel V. Maniaol (2015)
The proponents thought of establishing a business to create a unique and desirable kiosk. DINUGUAN PUTOH is obviously a kind of food for every hungry Juan. But it is not just like any food; DINUGUAN PUTOH gives different twist on the food especially to the Dinuguan. The proposed name of the project will be "DINUGUAN PUTOH" that came from the combination of the words "Dinuguan and Puto". Obviously, the proponents decided to add letter H to the establishment name for the customers to notice it in a funny remarkable way.
Undergraduate Feasibility Study